Response to docetaxel and cisplatin induction chemotherapy of locally advanced head and neck squamous cell carcinoma: a multicenter, non-comparative, open-label interventional pilot study. Issue 9 (26th July 2016) - Noronha, V; Goswami, C; Patil, S; Joshi, A; Patil, V M; Murthy, V; Arya, S; Juvekar, S; Goud, S; Prabhash, K
Abstract: Background: Docetaxel, cisplatin plus 5-fluorouracil is an efficacious induction regimen but is more toxic than cisplatin plus 5-fluorouracil. This study aimed to determine whether docetaxel and cisplatin without 5-fluorouracil maintains efficacy while decreasing toxicity. Methods: A multicenter non-comparative pilot study of locally advanced squamous cell carcinoma of the head and neck was performed. Patients received primary therapy comprising three cycles of 75 mg/m 2 docetaxel and 75 mg/m 2 cisplatin followed by concurrent chemoradiotherapy. The primary endpoint was the response rate to the docetaxel and cisplatin induction regimen. Results: A total of 26 patients were enrolled: of these, 23 (88.5 per cent) received all three docetaxel and cisplatin cycles. Common grade 3–4 adverse events were febrile neutropenia (19.2 per cent of patients), diarrhoea (19.2 per cent) and non-neutropenic infection (15.4 per cent). The overall response rate to docetaxel and cisplatin induction chemotherapy was 65.4 per cent. A total of 23 patients (88.5 per cent) subsequently received chemoradiotherapy with a median radiotherapy dose of 70 Gy. The response rate to chemoradiotherapy was 73 per cent. At a median follow up of 44 months, the 3-year progression-free survival and overall survival rates were 62 per cent and 69 per cent, respectively. Conclusion: Docetaxel and cisplatin induction chemotherapy is a feasible induction regimen with comparable efficacy to docetaxel, cisplatin and 5-fluorouracil induction chemotherapy.